A people's view of forestry aid - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Whose trees? by Mohamed Ahmed Hisham, Jan Sharma, Anthony Ngaiza and Nicholas Atampugre 1991